Pengaruh Pemberian Kredit Usaha Rakyat (KUR) BRI Unit Bualemo Terhadap Pertumbuhan Wirausaha di Desa Nipa Kalemoan Kecamatan Bualemo Kabupaten Banggai - Yelmi Tahawali; Usman Moonti; Agil Bahsoan; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
In addition, this research used a quantitative approach and the data were collected using observation, questionnaires, and documentation. Moreover, the population and the sample in this research were all 30 customers of BRI Bualemo Unit, The data were then analyzed through a simple linear regression analysis. The research results showed that giving Loans for People’s Business (KUR) positively affected Entrepreneurial Growth in Nipa Kalemoan Village, Bualemo Subdistrict, Banggai Regency. From the calculation of the coefficient of determination, it showed that the R square was 0.602, which meant that 60.2% of the variability of Entrepreneurial Growth (Y) in Nipa Kalemoan Village, Bualemo Subdistrict, Banggai Regency can be explained by the variable of giving Loans for People’s Business (KUR) (X), while other variables explained the remaining 39.8%.